Edukasi Gemar Makan Ikan Melalui Cerita Panggung Boneka di Sekolah Dasar Negeri 178 Pekanbaru - Rina D'rita Sibagariang; Budijono Budijono; Asmika H Simarmata; Isma Mulyani; Andri Hendrizal; Chicka Willy Yanti; Putriana Sari Sirait (PELANTAR PRESS, 2023)
Indonesia is a maritime country and an archipelagic country. Indonesia has abundant and diverse fish resources. Abundant fish resources make fish easy to obtain and cheap. However, there are still many people who do not like to consume fish and do not know the benefits contained in the body of fish. This activity aims to provide education about eating fish through puppet stories, so that students understand the benefits of fish in body growth. Community service activities were carried out on November 2, 2022 at the 178 Pekanbaru Elementary School, which were attended by 152 students. The method used is pretest and posttest design. From the results of the activity, it appears that in the pretest activities only a few students already know about the types of fish, the nutritional content of fish, the benefits of eating fish, and processed fish products. Then during the posttest, many students were able to answer and provide explanations regarding the types of fish, fish content, benefits of fish, and processed fish products. This service activity is expected to increase students insight and knowledge about types of fish, nutritional content, benefits of eating fish, processed fish products so that it is hoped that in the future students will like to eat fish.